Interactivia.ro – A study of a gamification framework using zero-cost tools. (August 2016) - Maican, Catalin; Lixandroiu, Radu; Constantin, Cristinel
Abstract: It is a fact beyond doubt that humans, irrespective of race, age or gender, love to play, games being considered a tool for enjoying oneself and relaxing, but also for one's mental and physical development. The present paper addresses the concept of gamification, tightly connected to games and playing. The first part of the paper makes an introduction to this concept, with an emphasis on how it could bring motivation in education and learning. Gamification is considered critically, with reference to some problems that could occur for applications using gamification for learning. The second part deals with the zero-cost implementation process of the Interactivia.ro platform, which uses gamification to develop general knowledge, showing how a playful social experience is doubled by educational usefulness. We developed a list of features required for a successful implementation using open source or freemium modules and we applied them to several modules identified on the market. The statistical analysis of the date resulting from the implementation revealed that gamification increases web traffic. We also highlighted how Interactivia.ro can alter the virtual gamified experience into one applied in real life through partnerships and discounts offered to its users. The final part of the paper presents the conclusions and the possible openings for improving the current business model. Highlights: Gamification framework using zero-cost tools. Platform for developing general knowledge. Tool validation using time-series, proving that gamification increasing traffic. Bringing gamification in the real world using partnerships.